The Management Of Character Education At School ‎(Analysis Study At Surakarta Public Secondary School)‎ - Rismiyati Nurindarwati (ATTARBIYAH: Journal of Islamic Culture and Education, 2019)
Character education is a system to instil character values to students including the components of awareness, understanding, consideration, and profound commitment in implementing those character values. The character education applies at Surakarta public secondary school (SMPN Surakarta) to encourage character values to students on the components of knowledge, awareness, and interest for God the Almighty, individual, other people, and society. Character education at schools closely relates to management or school evaluation that how character education is planned and applied properly at schools. In planning character education, it can immerse character values into learning. The implementation itself tries to integrate character education contents that have been formulated into all learning subjects. The integration is in all aspects of school daily basis life such as teacher role models in behaving and teaching. The success of character education is evaluated by the achievement of indicators of output competency standard such as performing religious teaching properly, following social norms, capable to think logically, critically, creatively and innovatively,  mastering knowledge for further education, and understanding personal and people rights and obligations during the life of local and national society.